Asymptomatic gossypiboma with complete intramural migration and ileoileal fistula - Singhal, Pranav Mohan (BMJ Case Rep, 2019)
Retained gossypiboma is a rare and under-reported complication of surgery, which can present in a variety of ways. Thus, a very high index of suspicion is required by the clinician to clinch the diagnosis in a postoperative patient. A 45-year-old woman, who was otherwise asymptomatic, presented to the General Surgery outpatient department (OPD) with a contrast-enhanced CT suggestive of a retained intra-abdominal foreign body from previous surgery. An exploratory laparotomy was planned on elective basis. Intraoperatively, dense inter-bowel adhesions were found in the upper abdomen. After a meticulous adhesiolysis, an ileoileal fistula and an intraluminal surgical sponge were discovered. Resection and anastomosis of the involved ileal segment was done. An asymptomatic patient with a migrated intramural gossypiboma with an ileoileal fistula is an extremely rare occurrence. In these circumstances, it becomes almost impossible for the surgeon to clinch the diagnosis of a gossypiboma in an otherwise asymptomatic patient, without the aid of radiological investigations.